Aplikasi Teori Model Jean Watson Dengan Penerapan Slow Deep Breating Pada Pasien Hipertensi Dengan Di Puskesmas Talangleak Kabupaten Lebong Tahun 2022 - Hartati, Herlis; Mariza, Mariza; Sofais, Danur Azissah roeslina (Universitas Dehasen Bengkulu, 2023)
Intoduction: Hypertension is a systemic blood pressure in which systolic pressure>140 mmHg and dystolic >90 mmHg. High blood pressure or hypertension is a medical condition in which there is a chronic increase in blood pressure (over a long period of time). People who have at least three blood pressure readings that exceed 140/90 mmHg at rest are thought to have high blood conditions. Always high blood pressure is one of the risk factors for stroke, heart attack, heart failure and arterial aneurysm, and is a leading cause of chronic heart failure.The general purpose of this study is to apply the application techniques of Jean Watson's theory to the application of slow deep breating to patients. This nursing concept model is used in determining the nursing practice model that will be applied according to the conditions and situations where the nurse works. Given that the nursing practice model contains basic components such as the beliefs and values that underlie a model, the existence of practice goals to be achieved in providing nursing services or care to the needs of all patients, and the knowledge and skills needed by nurses in achieving goals set according to patient needs.This case study research method uses a nursing process approach based on the chosen nursing theory, the techniques used in data collection are interviews, observations, physical examinations and conducting nursing care. The source of data obtained or used is primary obtained directly from patients and secondary data obtained from family, health workers and documentation from other examination results to carry out nursing care, while literature study is to study source books related to nursing care given to patients.The result of the application of slow deep breating in hypertensive patients is that patients feel happy and the nursing process is derived from the system and adapted to patients who have dedicated their articulation to nurses in using equipment for good practice, education, and research.